Endothelial-Mesenchymal Transition or Functional Tissue Regeneration - Two Outcomes of Heart Remodeling - Šalingová, B; Červenák, Z; Adamičková, A; Chomanicová, N; Valášková, S; Gažová, A; Kyselovič, J (Physiological research, 2021)
Heart remodeling occurs as a compensation mechanism for the massive loss of tissue during initial heart failure and the consequent inflammation process. During heart remodeling fibroblasts differentiate to myofibroblasts activate their secretion functions and produce elevated amounts, of extracellular matrix (ECM) proteins, mostly collagen, that form scar tissue and alter the normal degradation of ECM. Scar formation does replace the damaged tissue structurally; however, it impedes the normal contractive function of cardiomyocytes (CMs) and results in long-lasting effects after heart failure. Besides CMs and cardiac fibroblasts, endothelial cells (ECs) and circulating endothelial progenitor cells (cEPCs) contribute to heart repair. This review summarizes the current knowledge of EC-CM crosstalk in cardiac fibrosis (CF), the role of cEPCs in heart regeneration and the contribution of Endothelial-mesenchymal transition (EndoMT).
Keywords: endoteliální buňky; kardiomyocyty; endoteliální progenitorové buňky; transdiferenciace buněk; regenerace; lidé; srdce; interakce mezi receptory a ligandy; remodelace komor; Endothelial Progenitor Cells; Heart; Endothelial Cells; Regeneration; Ventricular Remodeling; Humans; Cell Transdifferentiation; Myocytes, Cardiac; Receptor Cross-Talk